Diseño de una red de tubería para aceite térmico en un equipo termofijador de la empresa Protela S.A. (2025)
The objective of this project is to design a piping network for the supply of thermal oil to the heat-setting equipment of the textile company Protela S.A. The implementation of this system will improve the energy efficiency of the fabric drying process, reducing problems such as contamination of light textiles and thermal losses associated with previous methods based on gas burners. For the design of the system, a survey of information about the area and the equipment was carried out, considering aspects such as thermal resistance, pipe flexibility, pressure losses and structural safety. Standards such as ASME B31.1 and B16 were used, as well as specialized software tools, including Autodesk AutoCAD Plant 3D, Pipe Flow Expert and CAESAR II, for modeling, stress analysis and support design.